DOES CORPORATE SOCIAL RESPONSIBILITY DRIVE COMPETITIVENESS OF SMALL AND MEDIUM SIZED ENTERPRISES: EVIDENCE FROM FIRMS IN HARARE - Upenyu Sakarombe; Charlotte Nyarunga (Jurnal Ekonomi dan Bisnis Airlangga, 2026)
Introduction: Corporate social responsibility (CSR) has increasingly been adopted by firms as a strategic tool to enhance competitiveness, particularly in developing economies. However, empirical evidence on its role among small and medium-sized enterprises (SMEs) in Zimbabwe remains limited. This study investigates the relationship between CSR practices and the competitiveness of SMEs operating in Harare, Zimbabwe. Methods: A quantitative research design was employed. Data were collected using self-administered questionnaires distributed to owners and managers of SMEs. Descriptive statistics, correlation analysis, and multiple regression analysis were used to analyze the data. Results: The findings reveal that environmental-oriented and market-oriented CSR practices have a significant positive effect on SME competitiveness, while workforce-oriented CSR practices were not statistically significant. Conclusion and suggestion: The study concludes that SMEs should prioritize environmental and market-oriented CSR initiatives to enhance competitiveness. The findings contribute to the limited CSR literature in the Zimbabwean SME context.